Hubungan Pemeriksaan dan Penagihan Pajak pada Penerimaan Pajak di Indonesia - Elia Rossa; Putri Afrilia Nurrochmah; Saefani Nur Hanifah; Salsabila Salsabila; Siska Aprilia Rahmawati; Siti Maisa Zahara; Yosi Ika Putri (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study explores the consequences of the tax audit and collection process on total tax revenue in Indonesia. By adopting the literature analysis method and assessing secondary data from the Directorate General of Taxes, the research findings reveal that tax audit and collection actions positively affect the level of tax revenue. A high frequency of tax audits is closely related to increased compliance and accumulated tax revenue. The same applies to the percentage of taxes successfully collected; the higher it is, the greater the level of compliance and tax revenue. Therefore, improvements in the efficiency of the government's implementation of tax audits and collections are needed to increase the overall level of compliance and tax revenue.